2020
DOI: 10.1371/journal.pone.0226581
|View full text |Cite
|
Sign up to set email alerts
|

A lower psoas muscle volume was associated with a higher rate of recurrence in male clear cell renal cell carcinoma

Abstract: BackgroundSarcopenia is defined as a low skeletal muscle volume. Recent studies have reported that sarcopenia is associated with a poor prognosis in various cancers. The purpose of this study is to evaluate the correlation between the psoas muscle volume and recurrence-free survival in patients with localized clear cell renal cell carcinoma (ccRCC). MethodsA total of 316 male patients with localized ccRCC who underwent radical nephrectomy at Yokohama City University Hospital (Yokohama, JAPAN) and Kanagawa Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…The PMI is calculated by normalizing the psoas muscle area for the height in meters squared. Our previous report showed that the whole psoas volume was correlated with psoas area at the L3 level [2]. The present study revealed that a low PMI was associated with a poorer prognosis than a high PMI in penile cancer, findings that concurred with those of previous reports in other solid malignancies [8,[11][12][13][14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The PMI is calculated by normalizing the psoas muscle area for the height in meters squared. Our previous report showed that the whole psoas volume was correlated with psoas area at the L3 level [2]. The present study revealed that a low PMI was associated with a poorer prognosis than a high PMI in penile cancer, findings that concurred with those of previous reports in other solid malignancies [8,[11][12][13][14].…”
Section: Discussionsupporting
confidence: 92%
“…The psoas muscle index (PMI) was calculated based on preoperative axial computed tomography (CT) images at the L3 level using the following formula: [right psoas muscle area (mm 2 )]/[body height (m)] 2 . We compared the progression-free survival (PFS) and overall survival (OS) of the higher and lower PMI groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the HR in each side of PMID showed differences. Our previous report also revealed that the both psoas muscle volume were correlated 10 . Though the meanings of differences between right and left, both PMID would be a useful factors to predict prognosis.…”
Section: Discussionmentioning
confidence: 84%
“…Our previous report also revealed that the both psoas muscle volume were correlated. 10 Abbreviations: Alb, albumin; ALP, Alkaline phosphatase; Cre, creatinine; Hb, hemoglobin; LDH, lactate dehydrogenase; PMID, psoas muscle index density; PSA, prostate-specific antigen.…”
Section: Discussionmentioning
confidence: 99%